Pengaruh prosentase etanol pada oli terhadap lidah api dan temperatur pada burner oli bekas - Mochammad Rizky Kurniawan; Djoko Wahyudi; Alief Muhammad (TURBO [Tulisan Riset Berbasis Online], 2021)
The large amount of used oil waste in Indonesia cannot be separated from the large number of industries that exist today. Apart from the large number of industries, used oil also comes from the remnants of the use of motor vehicles. types of Hazardous and Toxic Waste (B3) according to Government Regulation no. 8 of 1999. Used oil burners can be used as alternative fuels, of course this can solve the problems of Micro, Small and Medium Enterprises (MSMEs). The research method was carried out to determine the effect of a mixture of ethanol and oil on the length of the flame and temperature, then the researcher tried to determine the effect of the mixing time of ethanol and oil on the length of the flame and temperature. The research was carried out in the Mechanical Engineering laboratory of Panca Marga University in a closed state so that the flames did not change, taking pictures of the length of the flames by recording the fire propagation for 1 minute, then cutting each frame with the help of the imagej application. The results obtained from the study are the addition of the percentage of ethanol affects the length of the flame and the temperature produced by the burner.